Bacterial DNA amplifies neutrophilic inflammation in IL-17-exposed airways. Issue 1 (23rd January 2023) - Mues, Nastaran; Martin, Richard J.; Alam, Rafeul; Schaunaman, Niccolette; Dimasuay, Kris Genelyn; Kolakowski, Christena; Wright, Clyde J.; Zheng, Lijun; Chu, Hong Wei
Background: Neutrophilic asthma (NA) is associated with increased airway interleukin (IL)-17 and abnormal bacterial community such as dominance of nontypeable Haemophilus influenzae (NTHi), particularly during asthma exacerbations. Bacteria release various products including DNA, but whether they cooperate with IL-17 in exaggerating neutrophilic inflammation is unclear. We sought to investigate the role of bacteria-derived DNA in airway neutrophilic inflammation related to IL-17-high asthma and underlying mechanisms ( e.g. Toll-like receptor 9 (TLR9)/IL-36γ signalling axis). Methods: Bacterial DNA, IL-8 and IL-36γ were measured in bronchoalveolar lavage fluid (BALF) of people with asthma and healthy subjects. The role of co-exposure to IL-17 and bacterial DNA or live bacteria in neutrophilic inflammation, and the contribution of the TLR9/IL-36γ signalling axis, were determined in cultured primary human airway epithelial cells and alveolar macrophages, and mouse models. Results: Bacterial DNA levels were increased in asthma BALF, which positively correlated with IL-8 and neutrophil levels. Moreover, IL-36γ increased in BALF of NA patients. Bacterial DNA or NTHi infection under an IL-17-high setting amplified IL-8 production and mouse lung neutrophilic inflammation. DNase I treatment in IL-17-exposed and NTHi-infected mouse lungs reduced neutrophilic inflammation. Mechanistically, bacterial DNA-mediated amplification of neutrophilic inflammation is in part dependent on the TLR9/IL-36γ signalling axis. Conclusions: Bacterial DNA amplifies airway neutrophilic inflammation in an IL-17-high setting partly through the TLR9 and IL-36γ signalling axis. Our novel findings may offer several potential therapeutic targets including TLR9 antagonists, IL-36γ neutralising antibodies and DNase I to reduce asthma severity associated with exaggerated airway neutrophilic inflammation. More bacterial DNA was found in airways of asthmatics with neutrophilic inflammation. Bacterial DNA along with IL-17 amplified neutrophil chemokine production and airway neutrophil influx, which was reduced by an IL-36γ neutralising antibody or DNase I. https://bit.ly/3k9zkj4